A comparison of methods of measuring occlusal vertical dimension befor and after eduntulism. - حويجي, ذوالفقار; محمود محمود, (Latakia University Journal -Medical Sciences Series, 2024)
Introduction: Edentulous patients have special treatment among practicing doctors due the challenges they face in simulating the patients previous situation,and one of these challenges is restoring symmetry and harmony to the face.The most important factor on which this mechanism is based in the lower third of the face is occlusal vertical dimension of the face. Materials and Methods: The study sample included 30 paients with preserved vertical dimension and remaining teeth in one or both jaws for which extraction based was indicated .The occlusal vertical dimension was recorded for each patient before extraction based on reference points that were identified and preserved using vacuum plates for the nose and chin. After the extraction the reference points were determined .We measure the occlusal vertical dimension in several ways(pronouncing the letter M, swallowing ,pronouncing the letter O ,pronouncing the letter E) and these measurements are compared with the occlusal vertical dimension before the extraction. Results: The results of the statistical analysis showed: The is no difference between the occlusal vertical dimension before extraction and values (M-2) during the entire observation period. The is no difference between the occlusal vertical dimension before extraction and values( O-5.5)during the entire observation period. The is no difference between the occlusal vertical dimension before extraction and values (swallowing-2) during the two weeks after extraction. The is no difference between the occlusal vertical dimension before extraction and values( E-7.5) during the entire observation period. Conclusions: The (M-2),(O-5.5) methods can be adopted in determining the occlusal vertical dimension. The (E-7.5) cannot be adopted in determining the occlusal vertical dimension